2022
DOI: 10.2166/hydro.2022.132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of classic object-detection techniques for automated sewer defect detection

Abstract: Sewer systems play a key role in cities to ensure public assets and safety. Timely detection of defects can effectively alleviate system deterioration. Conventional manual inspection is labor-intensive, error-prone and expensive. Object detection is a powerful deep learning technique that can complement and/or replace conventional inspection manner, especially in complex environments. This study compares two classic object-detection methods, namely faster region-based convolutional neural network (R-CNN) and Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The emergence of deep learning techniques has better addressed the drawbacks of traditional computer vision methods. As the most popular algorithm among them, convolutional neural network (CNN) is most widely used [10]. Compared with the traditional CV method, CNN can automatically extract image features and perform recognition, without the need for professional technicians with rich work experience and complex feature design process, which greatly simplifies the detection process.…”
Section: Sewer Defect Detection Based On Deep Learning Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of deep learning techniques has better addressed the drawbacks of traditional computer vision methods. As the most popular algorithm among them, convolutional neural network (CNN) is most widely used [10]. Compared with the traditional CV method, CNN can automatically extract image features and perform recognition, without the need for professional technicians with rich work experience and complex feature design process, which greatly simplifies the detection process.…”
Section: Sewer Defect Detection Based On Deep Learning Techniquesmentioning
confidence: 99%
“…The method demonstrates the high accuracy of CNN in sewer defect classification tasks and has been applied to practical inspection tasks. However, this method can only detect one type of defect on a single image, whereas sewer pipes may have multiple types of defects at the same location [10].…”
Section: Sewer Defect Identification Based On Image Classification Te...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, object detection architectures are mainly classified into anchorfree models [14], single-stage models [15], two-stage models [2], and multi-stage models [16]. It has been shown that two-stage is more likely to achieve superior precision than single-stage when there is more training data on sewer defects [17]. Inspired by previous work, a novel multi-stage object detection model based on a composite backbone Swin Transformer is designed for detecting sewer defects.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of deep learning technology, object detection technology that can perform both classification and detection is widely used for vehicle recognition [4], hand script counterfeit detection [5], and automatic detection of drainage sewers in China and abroad [6,7]. The most commonly used methods include Single Shot Multibox Detector (SSD) [8], You Only Look Once (YOLO) [9], and Faster RCNN [10], which effectively improve the detection accuracy by using neural networks to automatically extract features.…”
Section: Introductionmentioning
confidence: 99%